STATUS MENTAL EMOSIONAL KARYAWAN UNIVERSITAS BHAKTI KENCANA SAAT MENJALANI WORK FROM OFFICE - Vina Vitniawati; Anggi Jamiyanti (Departemen Psikologi Universitas Pendidikan Indonesia, 2021)
AbstractThe world is currently experiencing a pandemic due to COVID-19. Indonesia is one of the countries affected and affected by this virus. Government policies as a measure to prevent and handle COVID-19 ranging from Large-Scale Social Restrictions (PSBB) to policies in the New Normal Era. This policy has an impact on employees who were previously Work From Home (WFH) to Work From Office (WFO). Working in pandemic conditions and situations raises worries at work so that it has an impact on mental and emotional status which affects work productivity. The purpose of this study was to determine the emotional mental status of the Bhakti Kencana University employees while undergoing a work form office. This research method uses descriptive method on employees who undergo Work From Office as many as 69 people using the SRQ 29 instrument. The results show that long Underwent work from office as much as 29.0 percent experienced symptoms of anxiety and depression, 15.9 percent experienced psychotic disorders, 68.1 percent experienced post-traumatic stress disorder, 17.4 percent did not experience changes in mental emotional status and none experienced any disturbances. psychoactive and drug use. The mental and emotional changes of employees during work from office will affect employee work productivity, besides the physiological impact when the body experiences psychological disorders will reduce immunity, thereby increasing the risk of COVID-19 transmission. The results showed that there was a change in the mental emotional status of employees during work from office. Improved coping mechanisms by increasing knowledge about Covid 19, health protocols at work, flexibility at work and health insurance for employees can reduce the psychological impact while working from office in the era the COVID-19 pandemic AbstrakDunia saat ini mengalami pandemic akibat COVID-19. Indonesia merupakan salah satu negara yang terkena dan terdampak akibat virus ini. Kebijakan pemerintah sebagai langkah pencegahan dan penanganan COVID-19 mulai dari Pembatasan Sosial Berskala Besar (PSBB) sampai kebijakan di Era New Normal. Kebijakan ini berdampak pada karyawan yang sebelumnya Work From Home (WFH) menjadi Work From Office (WFO). Bekerja dalam kondisi dan situasi pandemic meberikan kekhawatiran saat bekerja sehingga berdampak pada status mental dan emosional yang mempengaruhi produktivitas bekerja. Tujuan penelitian ini untuk mengetahui status mental emosional karyawan Univeritas Bhakti Kencana saat menjalani work form office. Metode Penelitian ini menggunakan metode deskriptif pada karyawan yang menjalani Work From Office sebanyak 69 orang menggunakan instrument SRQ 29. Hasil penelitian menunjukan selama menjalani work from office sebanyak 29,0 persen mengalami gejala cemas dan depresi, 15,9 persen mengalami gangguan psikotik, 68,1 persen mengalami post-traumatic stress disorder, 17,4 persen tidak mengalami perubahan status mental emosional dan tidak ada yang mengalami gangguan psikoaktif dan penggunaan narkoba. Perubahan mental dan emosional saat menjalani work from office akan berpengaruh secara fungsi fisiologi sehingga meningkatkan kerentanan penularan dan berdampak produktivitas pekerjaan. Sehingga institusi harus meningkatan mekanisme koping dengan meningkatkan pengetahuan tentang COVID-19, mempertahankan protokol Kesehatan, fleksibilitas dan jaminan kesehatan saat bekerja di era pandemic COVID-19.